Semiquantitative Bacterial Observations With Group B Streptococcal Vulvovaginitis - G. R. G. Monif (Hindawi Limited, 1999)
Objective: Group B streptococcal (GBS) vulvovaginitis is a poorly-delineated clinical entity. The purpose of this study is to report semiquantitative data from four cases of GBS vulvovaginitis and to comment on their significance in terms of the in vitro inhibitory capabilities of GBS.